PENGARUH PEMBERDAYAAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DENGAN BUDAYA ORGANISASIONAL SEBAGAI VARIABEL MODERASI ( Studi pada DPPKAD Kabupaten Batang ) - Juniarto, Triossy (Students Journal of Economic and Management, 2012)
The purpose of this study was to implementation to test and analyze the effect on the performance of an employee empowerment, motivation on employee performance, organizational culture on employee performance, employee empowerment on performance with moderation organizational culture and work motivation on employee performance with organizational culture moderation The research was conducted at the Department of Finance and Asset Management Revenue District Trunk numbering 87. Sampling technique using census. The results of regression testing obtained results Adjusted R Square of 0.857, meaning that the change of variable performance can be explained by the variable employee empowerment, motivation and organizational culture at 85.7%, while for the F test showed that together empowerment, motivation and organizational culture affects employee performance. Based on the known partial regression testing empowering effect on performance with significance 0.014 <0.05, work motivation on performance with significance 0.014 <0.05 and organizational culture affect the performance of the significance 0.000. <0.05. It is identified that all the hypotheses accepted or proven. Testing moderation empowerment on employee performance with organizational culture moderation with significance 0.07 <0.05 and testing moderation motivation on the performance of the moderating organizational culture with significance 0.001 <0.05. It proved that organizational culture is a moderating variable. Key word : Empowerment, Motivation Work, Organizational Culture and Employee Performance